Fascicular shifting in the reconstruction of brachial plexus injuries: an anatomical and clinical evaluation - Sporer, Matthias; Brugger, Peter C.; Aman, Martin; Fuchssteiner, Christoph F.; Festin, Christopher; Gstoettner, Clemens; Aszmann, Oskar C. (Journal of neurosurgery, 2022)
OBJECTIVE: Until recently, autologous sensory nerve grafting has remained the gold-standard technique in peripheral nerve reconstruction. However, there are several disadvantages to these grafts, such as donor site morbidity, limited availability, and a qualitative mismatch. Building on this shortage, a new concept, the fascicular shift procedure, was proposed and successfully demonstrated nerve regeneration in a rat nerve injury model. This approach involves harvesting a fascicular group distal to a peripheral nerve injury and shifting it to bridge the defect. The present study aimed to evaluate the clinical applicability of this technique in brachial plexus reconstruction. METHODS: The supra- and infraclavicular nerves of the brachial plexus were bilaterally explored in 18 formalin-fixed cadaveric specimens. Following dissection, their fascicular shifting potential was evaluated. The medial antebrachial cutaneous and sural nerves were investigated and used as references for the required cross-sectional area of potential nerve grafts. Furthermore, 29 brachial plexus injuries, which qualified for surgical repair, were subjected to retrospective analysis. The intraoperatively measured lengths of the harvested and ultimately transplanted nerve grafts served as a basis to assess graft requirements in brachial plexus lesions. RESULTS: The transplanted nerve grafts measured a total length of 51.9 ± 28.1 cm in brachial plexus injuries. The individual inserted nerve grafts averaged 10.3 ± 5.1 cm. In the anatomical exploration, the ulnar and median nerves qualified for fascicular shifting. Their fascicular graft lengths measured 26.6 ± 2.5 cm and 24.8 ± 5.2 cm, respectively. The long thoracic, suprascapular, musculocutaneous, thoracodorsal, and axillary nerves were not suitable for fascicular shifting. The sensory graft length of the medial antebrachial cutaneous nerve measured 20.6 ± 3.4 cm. CONCLUSIONS: In the surgical reconstruction of brachial plexus injuries, fascicular shifting of the ulnar and median nerves provides sufficient donor material. Even though potential donor length is limited in the radial nerve, it may still help to expand the surgical armamentarium in selected clinical scenarios. Overall, the fascicular shift procedure presents a novel alternative to allow modality-matched grafting in the reconstruction of large proximal nerve defects and was found to be an attractive option in brachial plexus reconstruction.